2022
DOI: 10.1002/imt2.15
|View full text |Cite
|
Sign up to set email alerts
|

iMeta: Integrated meta‐omics for biology and environments

Abstract: The cover of iMeta's inaugural issue. The galaxy represents the complexity and value of bioinformatics and metagenomics. DNA, which represents genetic components that guide biological diversity, is at the center of the galaxy. The spiral arms are the microbiome welcoming scientists from all over the world to make novel discoveries. Let us usher in the metaverse era of the microbiome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Microbiome research has experienced major technical, practical, and conceptual progress in recent years ( Lynch et al, 2019 ; Liu et al, 2022 ). During the early days, the initial focus was to describe the composition and diversity of microbiomes and to identify correlations between microbes and host phenotypes.…”
Section: Global Trends and Advancements In Microbiome Research: From ...mentioning
confidence: 99%
“…Microbiome research has experienced major technical, practical, and conceptual progress in recent years ( Lynch et al, 2019 ; Liu et al, 2022 ). During the early days, the initial focus was to describe the composition and diversity of microbiomes and to identify correlations between microbes and host phenotypes.…”
Section: Global Trends and Advancements In Microbiome Research: From ...mentioning
confidence: 99%
“…The structural composition of the gut microbiota is the result of strong selection and co-evolution between the host and its environment, and studies in a variety of mammals (e.g., humans, ruminants, rabbits, rhesus macaques, mice, etc.) have confirmed that the gut microbiota positively contributes to the adaptation of its hosts to high-altitude environments 2,[10][11][12][13][14] . Metabolites, such as short-chain fatty acids (SCFAs), bacteriocins, and bacterial proteins produced by gut microbiota, play important roles in host metabolic regulation, energy replenishment, and immune regulation [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 69%
“…These explorations contribute to a deeper understanding of how TCM, through modulating gut microbiota, can offer therapeutic benefits, thus providing insights into new treatment strategies and drug discoveries. Most of the nine presentations at the iMeta Author Forum showcased eye-catching publications from the iMeta journal [8]. This forum explored various aspects of microbiome analysis, bioinformatics visualization, and the development of analytical tools [9].…”
Section: Gut and Traditional Chinese Medicine (Tcm)mentioning
confidence: 99%